Survey of euthanasia methods used in neotropical chiropterans in São Paulo State, Brazil: critical analyses and proposal for standardization of bat euthanasia methods - Lauri, Liura Sanchez; Souza, Alex Junior Souza de; Scheffer, Karin Corrêa; Mori, Enio; Sá, Lilian Rose Marques de (Brazilian Journal of Veterinary Research and Animal Science, 2023)
Zoonotic Surveillance Divisions (ZSDs) rescue and euthanize bats in contact with humans. The euthanasia procedure should be conducted safely for the animal and caretaker and minimal stress for the animal is important. The objectives of this study were: i. evaluate the methods of euthanasia used by ZSDs in the State of São Paulo; ii. compare the methods with national and international guidelines for animal euthanasia practices; iii. assess the methodologies considering taxonomy and eating habits of the main bat species, and iv. propose standardization of euthanasia procedures. Sixty-five ZSDs locations received an online questionnaire or were contacted by telephone and 33 ZSDs (50.8%) responded and are distributed in 11 mesoregions in the state to remain anonymous. The euthanasia methods were divided into chemical (injectable or inhalation), physical, or mixed methods. Bat specimens (n = 550) were identified and classified to evaluate the main genera found in the state. The location of the ZSD, species, eating habits, and the method of euthanasia used were analyzed. The specimens by bat families were Molossidae (n = 340), Phyllostomidae (n = 171), and Vespertilionidae (n = 39). Chemical methods were used in 25 ZSDs (75.75%), physical in 5 (15.15%), and mixed in 3 (9.09%). There is no uniformity or standardization in bat euthanasia methods used by ZSDs, although most are based on acceptable chemical methods. It was proposed an algorithm to assist the veterinarian in choosing the method of euthanasia for bats that will allow standardizing euthanasia procedures for this species, considering physiological differences, and respecting technical, bioethical, and animal welfare guidelines.